Β2‐Glycoprotein I binds to thrombin and selectively inhibits the enzyme procoagulant functions. Issue 6 (3rd July 2013) - Pozzi, N.; Acquasaliente, L.; Frasson, R.; Cristiani, A.; Moro, S.; Banzato, A.; Pengo, V.; Scaglione, G. L.; Arcovito, A.; De, R.; De, V.
Summary Background This work was aimed at characterizing the interaction of β2‐glycoprotein I (β2GPI), an abundant plasma protein of unknown function, with human thrombin, the final effector protease in the coagulation cascade. Methods The β2GPI–thrombin interaction was studied by surface plasmon resonance (SPR), fluorescence, and molecular modeling. The effect of β2GPI on the procoagulant (fibrin generation and platelet aggregation) and anticoagulant (protein C activation) functions of thrombin were investigated with turbidimetric, immunocytofluorimetric and enzymatic assays. Results SPR and fluorescence data indicated that β2GPI tightly bound thrombin (Kd = 34 nm) by interacting with both protease exosites, while leaving the active site accessible. This picture is fully consistent with the theoretical model of the β2GPI–thrombin complex. In particular, blockage of thrombin exosites with binders specific for exosite‐1 (hirugen and HD1 aptamer) or exosite‐2 (fibrinogen γ′‐peptide and HD22 aptamer) impaired the β2GPI–thrombin interaction. Identical results were obtained with thrombin mutants having one of the two exosites selectively compromised by mutation (Arg73Ala and Arg101Ala). Fluorescence measurements indicated that β2GPI did not affect the affinity of the enzyme for active site inhibitors, such as p‐aminobenzamidine and the hirudin(1–47) domain, in agreement with the structural model. β2GPI dose‐dependently prolonged the thrombin clotting time and ecarin clotting time in β2GPI‐deficient plasma. β2GPI inhibited thrombin‐induced platelet aggregation (IC50 = 0.36 μm) by impairing thrombin cleavage of protease‐activated receptor 1 (PAR1) (IC50 = 0.32 μm), both on gel‐filtered platelets and in whole blood. Strikingly, β2GPI did not affect thrombin‐mediated generation of the anticoagulant protein C. Conclusions β2GPI functions as a physiologic anticoagulant by inhibiting the key procoagulant activities of thrombin without affecting its unique anticoagulant function.